Antibiotic use patterns and trends in the FDMN population and rural Bangladeshi population: a cross-sectional study (Asian Journal of Medical and Biological Research, 2024)
Global antibiotic resistance is a pressing issue, especially in Bangladesh, due to its widespread use, poor surveillance, and high treatment costs. This study compared antibiotic use between Rohingya and rural Bangladeshi residents, aiming to predict the frequency and tendency of commonly used antibiotics across different community levels. This was a cross-sectional descriptive study using a questionnaire. It involved Cox's Bazar camp, Tangail, and Bogura rural areas. Most participants were male, with 46.8% graduates and 20.8% untrained from mixed economic backgrounds. The study revealed that 62% adhered to doctors' orders, 28.5% followed pharmacists' recommendations, 6% sourced antibiotics from various places, 3% self-medicated, and 1% relied on advice from friends or relatives. Alarmingly, 25.3% did not complete their antibiotic courses. Age, region, advisor status, and education level were correlated with antibiotic use (P